AB0559 Hypokalemic Paralysis in Primary Sjogren Syndrome: is IT A Distinct Clinical Subset Which Requires Lifelong Potassium Supplementation Rather than Immunosuppressants?. (10th June 2014) - Jain, V.K.; Antony, P.T.; Mithun, C.B.; Singh, B.K.; Mehra, S.; Usdadiya, J.; Negi, V.S.
Abstract : Background: Primary Sjögren's syndrome (pSS) is a systemic autoimmune disorder with predominant involvement of exocrine glands in middle aged females. It may involve extra-glandular tissues such as lung, liver, kidney, pancreas, skin, and central nervous system. Clinically significant renal involvement in pSS is rare and interstitial nephritis is the commonest histopathological finding 1 . The resulting tubular defects may present with failure to concentrate urine (hyposthenuria) and type I (distal) renal tubular acidosis characterized by hyperchloremic metabolic acidosis and hypokalemia. We describe a series of 15 cases of pSS who presented with hypokalemic periodic paralysis as the initial manifestation. Their clinical features; biochemical and immunological parameters are compared and contrasted with those without hypokalemic weakness. Objectives: To explore the clinical, biochemical, serologic features, and therapeutic responses in Primary Sjogrens syndrome (pSS) patients who presented with hypokalemic paralysis as the initial manifestation. Methods: Sixty patients of pSS (diagnosis based on modified European-American classification criteria) are on our follow up from November 2009 to August 2012. A few of these patients were diagnosed following admission to emergency services with hypokalemic paralysis. They were compared for differences in clinical features, biochemistry and serological parameters with pSS patients without hypokalemic paralysis. Results: Symptomatic hypokalemia was the presenting symptom in 15 out of 60 (25%) primary SS. All patients in the hypokalemic paralysis group were females and with a lower age of onset (27.8±8.3 vs 38.85±11.5 yrs). Six of 15 (40%) patients did not have the classical sicca symptoms. All patients with hypokalemic paralysis had biochemical features of distal renal tubular acidosis and high titers of anti SSA antibody. During a mean follow up of sixteen months, only two patient developed relapse of hypokalemic weakness following stoppage of potassium supplements. Conclusions: There exists a distinct subset of pSS who present with onset at younger age, distal RTA, hypokalemic paralysis and high titres of anti SSA antibody sometimes even without characteristic exocrinopathy. Genetic analysis may help in further characterization of these patients. Therefore, all young females presenting with hypokalemic paralysis should be investigated for underlying pSS. References: Andreas V. Goules, Ioanna P. Tatouli, Haralampos M. Moutsopoulos, Athanasios G. Tzioufas. Clinically Significant Renal Involvement in Primary Sjögren's Syndrome. Clinical Presentation and Outcome. Arthritis & Rheumatism.2013 Nov;65(11):2945–53 Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1739